2011
DOI: 10.1002/jbt.20396
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of MiRNA‐195 and its role in biogenesis, the cell cycle, and apoptosis

Abstract: microRNA-195(miR-195) is an important member of the micro-15/16/195/424/497 family, and which is activated in multiple diseases, such as cancers, heart failure, and schizophrenia. Mir-195 regulates a plethora of target proteins, which are involved in the cell cycle, apoptosis, proliferation. WEE1, CDK6, and Bcl-2 are confirmed target genes of miR-195 that are involved in miR-195-mediated cell-cycle and apoptosis effects. However, the mechanism of miR-195 action is not completely understood. This review summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 27 publications
1
70
0
1
Order By: Relevance
“…This highlights that the study of a single disease, such as laryngeal cancer, is advantageous over a combination study of various types of head and neck tumors in multiple sites. miR-195 is an important member of the miRNA-15/16/195/424/497 family that is downregulated in various types of cancer, including liver, gastric, breast, bladder cancer and chronic lymphocytic leukemia, which suggests that miR-195 may be an important tumor suppressor (30). The present study represents the first report to demonstrate that miR-195 has reduced expression in laryngeal cancer; however, further investigation is required to confirm this result at the cellular level.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights that the study of a single disease, such as laryngeal cancer, is advantageous over a combination study of various types of head and neck tumors in multiple sites. miR-195 is an important member of the miRNA-15/16/195/424/497 family that is downregulated in various types of cancer, including liver, gastric, breast, bladder cancer and chronic lymphocytic leukemia, which suggests that miR-195 may be an important tumor suppressor (30). The present study represents the first report to demonstrate that miR-195 has reduced expression in laryngeal cancer; however, further investigation is required to confirm this result at the cellular level.…”
Section: Discussionmentioning
confidence: 99%
“…miR-124 is a novel member of these miRNAs, which has been characterized as a tumor suppressor in human cancers by targeting critical cancer-related pathways. It is shown that miR-124 could affect the STAT3 signal pathway and enhance the anticarcinogenic effect [9][10][11]. Notably, a recent study indicated that miR-124 is associated with tumor metastatic capability; however, the role of miR-124 in GBM proliferation and invasion remains unknown.…”
Section: Introductionmentioning
confidence: 95%
“…Apoptosis, also called programmed cell death, is critical in normal development, and in the initiation and progression of cancers (39). Mutated and deleted pro-apoptotic genes give rise to carcinogenesis and tumor growth.…”
Section: Gas5 Tumor-suppressive Functionsmentioning
confidence: 99%